Research on life cycle of bulk port production environmental management information system. Issue 5 (February 2019) - Zhang, Chunyi
Abstract: Comprehensive information platform for port environmental management is necessary to be developed, due to the serious dust pollution and low efficiency of primary environmental protection equipment in the bulk port, which should be combined with life cycle of bulk port production and on the basis of the clean and efficient production needs. The aim of this study was to solve the port environmental management information platform framework, model selection and system development. It provides technical support for the establishment of port environmental management information system, realizes the automotive and global control of the port environment, and a breakthrough of the port environmental management practice.